Computers in our world, today and tomorrow - Hintz, Sandy; Hintz, Martin (New York : F. Watts, 1983)
Describes the roles of computers, now and in the future, in the spheres of medicine, business and government, law enforcement, science and technology, entertainment, education, and the home. Includes a glossary of terms.
Includes index.
ii 15/01/2019
Loans
Keywords: Computers; Electronic data processing; Computers; Data processing